Stress response for disease control in aquaculture - Yeong Yik Sung; Thomas H. MacRae; Patrick Sorgeloos; Peter Bossier (Blackwell Publishing Asia Pty Ltd, 2025)
Heat shock proteins (Hsps) are robustly induced by diverse stressors that denature proteins. In addition to stress resistance, Hsps are involved in the folding of nascent proteins, plant and animal development, aging, environmental adaptation and the immune response, demonstrating the fundamental importance of these proteins to cell survival. Heat shock proteins are induced in aquatic organisms by perturbations of temperature and salinity, environmental contaminants, handling, hormones and biotic stressors. Exposure to sublethal stress may enhance tolerance to a subsequent stress, a process termed induced thermotolerance, and provide protection to stressors other than the initial stress, known as cross-tolerance. In the present review, we briefly describe the established approaches that are used to control disease during aquaculture. This is followed by documentation of Hsp induction after exposure to stressors commonly encountered by aquatic organisms. Induced thermotolerance, cross-tolerance and immune enhancement by Hsps are also considered. Although physiological stress is known to decrease disease resistance it is now becoming clear that stress-induced Hsps enhance the tolerance of aquatic organisms to disease. Potential applications for Hsps in the commercial production of fish, crustaceans and molluscs are indicated, an issue of significance when the importance of aquaculture in feeding the world’s population is realized.